PENGARUH PENGGUNAAN MEDIA WORDWALL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI BILANGAN DESIMAL KELAS IV SDN NO 18 DUNGINGI KOTA GORONTALO - Marshanawiah, Andi; Khoifah, Aini; Sarlin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effect of the use of wordwall media on the ability to solve mathematical problems in grade IV decimal number material at SDN No.18 Dungingi, Gorontalo City. A quantitative test such as a pretest-posttest with the X variable in this exploration in the form of wordwall media and the Y variable in the form of mathematical problem-solving ability with saturated sampling, in 23 students in grade IV. The data collection methods are observation, interviews, tests, and documentation. Based on data before and after the test. The average value of the pretest parameters before being given the wordwall media treatment was 24.78, and the average value of the posttest parameters after being given the wordwall media treatment was 76.26 which means that H0 was rejected and H1 was accepted. This is supported by the results of the t-test which shows sig = 0.00 < 0.05, H0 rejected, H1 accepted, and the average N-Gain result of 0.67 including the medium criteria. This means that the use of wordwall media has an effect on the problem-solving ability in grade IV decimal number material at SDN No.18 Dungingi, Gorontalo City.